„Dumna inność”. Jarosław Iwaszkiewicz wobec własnej tożsamości terytorialnej. Wiersz dedykowany Antoniemu Sobańskiemu - Dubyk, Hałyna (Czytanie Literatury. Łódzkie Studia Literaturoznawcze, 2012)
The article “Dignified Distinctness”. Jarosław Iwaszkiewicz’s attitude toward his own territorial identity is an attempt to interpret the poem dedicated to Antoni Sobański in the light of the author’s Ukrainian identity, the lyrical subject and the work’s addressee. The analysis was based on the analyzed poem as well as other Ukrainian works by Jarosław Iwaszkiewicz, including his post-war works, in which the traces of the Ukrainian territorial identity (rarely found in his earlier texts) were reduced and selfcensored.